Real-world experience of emicizumab prophylaxis in young children with hemophilia A: retrospective data from China - Liu, Guoqing; Huang, Kun; Li, Gang; Zhen, Yingzi; Li, Zhengping; Chen, Zhenping; Wu, Runhui (Frontiers in Pediatrics, 2022)
Background As a new non-factor therapy for hemophilia A(HA), real-world study of emicizumab is still scarce. The aim of this study was to investigate the real-world use of emicizumab in Chinese boys with HA. Methods Patients with moderate or severe HA were enrolled at Beijing Children’s Hospital. They take emicizumab weekly(3mg/kg) for a month and then went into maintenance period with different dosing regimen. After obtaining platelet-poor plasma at end of loading period and during maintenance period, coagulation ability and FVIII inhibitor were determined using human and bovine chromogenic Bethesda assay. Patients’ bleeding rates were calculated through patients’ record from 24 weeks before to at least 6 months after the switch (to emicizumab). Result In total, 13 pediatric patients with HA (severe: moderate=11:2) were enrolled in this study. The patients’ age was 3.51(0.73-6.65) years. Eight had FVIII inhibitor at enrollment and one of them developed FVIII inhibitor again during the switch. The coagulation level of maintenance period was 19.6(13.5-32.8) IU/dL(N=10). The median dose of each emicizumab injection were 2.7 (1.3-3.8) mg/kg and the monthly consumption of emicizumab was 5.2(3.2-6.8) mg/kg/month. After switching to emicizumab, reduced ABR [0.5(0-4) vs. 4(0-18), P<0.01], AJBR [0(0-1.1) vs. 1.0(0-12), P<0.01] and ASBR[0(0-1) vs. 2.0(0-18), P<0.01] were observed. In patients with or without FVIII inhibitor, similar ABR [0.33(0-4) vs. 0.5(0-3),P=0.78], AJBR[0(0-1.1) vs. 0(0-0.5),P=0.63] and ASBR[0(0-1) vs. 0(0-1.5),P=0.73] were also noticed. Five inhibitor-positive patients (at enrollment) all had their inhibitor titer reduced. In addition, all target joints vanished after switching to emicizumab. Conclusion Emicizumab could reduce bleeds in pediatric patients with/without FVIII inhibitor and eliminate target joints.